Rational Emotive Behavior Therapy dan Konseling Islami: Studi Eksperimen untuk Mereduksi Perilaku Pornografi Siswa - Dewi, Hari Utami; Purwoko, Budi; Naqiyah, Najlatun (Universitas Nusantara PGRI Kediri, 2022)
This study discussed the implementation of REBT group counseling treatment, REBT group counseling, and Islamic counseling, as well as conventional group counseling. Aims to test the difference in effectiveness between the three treatment groups to reduce pornographic behavior for students of SMA Negeri 1 Sumenep. This research was a quantitative study with a Quasy Experimental design, with a control group and an experimental group. The sample used purposive sampling, namely students who had a high pornography score on a pornography scale of 22 students who were divided into 3 treatment groups. The research instrument was a questionnaire validated and supported by data sources, namely interviews, observations, and documentation. Data analysis used Anava, the normality test method using Shapiro-Wilk, and the homogeneity test using the Test of Homogeneity of Variances. The results of the normality test were normally distributed, which were classified as parametric, the results of the homogeneity test of all groups were homogeneous, while the results of the Anova one way were differences in the decrease in pornography behavior after receiving treatment compared to before treatment, and the REBT group counseling treatment and Islamic counseling were more effective than the other two treatments. . So pornographic behavior or deviant or immoral behavior should be reduced by using effective counseling methods and techniques to solve student problems.